SARS-CoV-2 strains bearing Omicron BA.1 spike replicate in C57BL/6 mice - Ogger, Patricia P.; Martín, Minerva Garcia; Jang, Soyeon; Zhou, Jie; Brown, Jonathan; Sukhova, Ksenia; Furnon, Wilhelm; Patel, Arvind H.; Cowton, Vanessa; Palmarini, Massimo; Barclay, Wendy S.; Johansson, Cecilia (Frontiers in Immunology, 2024)
SARS-CoV-2, the cause of the COVID pandemic, is an RNA virus with a high propensity to mutate. Throughout the pandemic, successive virus variants, including variants of concern (VOC), have emerged with increased transmission or immune escape properties. The original pandemic virus and early variants replicated poorly, if at all, in mice at least partly due to a mismatch between the receptor binding domain on the viral spike protein and the murine angiotensin converting enzyme 2 (ACE2). Omicron BA.1 emerged in late 2021 harboring >50 new mutations, 35 of them in the spike protein, and resulted in a very large wave of infections, even in the face of prior immunity, albeit being inherently less severe than earlier variants.Reflecting the lower severity reported in humans, Omicron BA.1 displayed attenuated infection in hamsters and in the K18-hACE2 mouse model. K18-hACE2 mice express both the human ACE2 as well as the endogenous mouse ACE2. Here we infected hACE2 knock-in mice that express only human ACE2 receptors and no murine ACE2, or C57BL/6 wildtype mice bearing murine ACE2 with SARS-CoV-2 D614G (first-wave isolate), Delta and Omicron BA.1 and assessed infectivity and downstream innate immune responses. While replication of SARS-CoV-2 Omicron BA.1 was lower in the lungs of hACE2 knock-in mice compared with SARS-CoV-2 D614G and Delta, it replicated more efficiently than the earlier variants in C57BL/6 wildtype mice. Given the availability of genetically-modified mice on the C57BL/6 background, this finding opens the opportunity to test the effect of host genetics on SARS-CoV-2 mouse infection. As a proof of principle, we tested Omicron BA.1 infection in C57BL/6 mice lacking the interferon-alpha receptor-1 (IFNAR1). In these mice, we found higher viral loads in the lungs. Finally, using a chimeric virus of first wave SARS-CoV-2 harboring the Omicron BA.1 spike protein, we show that the Omicron BA.1 spike increase infection of C57BL/6 WT mice, but non-spike genes of Omicron BA.1 confer attenuation of viral replication. Since this chimeric virus efficiently infected wildtype C57BL/6 mice, and replicated in their lungs, our findings illustrate an experimental pathway for genetic mapping of SARS-CoV-2 virus-host interactions.